2017
DOI: 10.1007/s11999-016-4747-x
|View full text |Cite|
|
Sign up to set email alerts
|

Reconstruction After Hemipelvectomy With the Ice-Cream Cone Prosthesis: What Are the Short-term Clinical Results?

Abstract: Background Reconstruction after internal hemipelvectomy resection likely provides better function than hindquarter amputation. However, many reconstruction methods have been used, complications with these approaches are common, and function often is poor; because of these issues, it seems important to investigate alternative implants and surgical techniques. Questions/purposes The purposes of this study were (1) to identify the frequency of surgical site complications and infection associated with the use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 34 publications
1
36
0
3
Order By: Relevance
“…Questions/purposes The purposes of this study were (1) to evaluate in a small case series whether the new endoprosthesis restored lower limb function and lumbopelvic stability in the short term; (2) to identify the complications associated with use of the new prosthesis; and (3) to assess the 5-year cumulative survival, the cumulative incidence of a major postoperative event, and the cumulative incidence of implant failure in this group of patients. Methods Between August 2012 and August 2014, our center performed 274 internal hemipelvectomies for oncologic indications.…”
mentioning
confidence: 99%
“…Questions/purposes The purposes of this study were (1) to evaluate in a small case series whether the new endoprosthesis restored lower limb function and lumbopelvic stability in the short term; (2) to identify the complications associated with use of the new prosthesis; and (3) to assess the 5-year cumulative survival, the cumulative incidence of a major postoperative event, and the cumulative incidence of implant failure in this group of patients. Methods Between August 2012 and August 2014, our center performed 274 internal hemipelvectomies for oncologic indications.…”
mentioning
confidence: 99%
“…Because of the tumor invasion of the proximal femur, it is often necessary to cut off the greater trochanter and lesser trochanter during the osteotomy, thus losing the anatomical markers as the reference for implanting the prosthesis stem [30]. Surgeons usually make marks on the junction before resecting the involved bone, and make marks on the corresponding part of the prosthesis stem to offer reference when implanting the prosthesis stem [31,32]. After implanting the prosthesis stem, it will be…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 13 , 14 Gebert et al 11 reported good results with a low infection rate of 3 in 17 patients subjected to medialization of the hip with femoral endoprosthesis implantation. Barrientos-Ruiz 15 had 10 wound and 2 deep infections in ten ice-cream-cone prosthesis implantations. Zeifang et al 5 suggested that biological reconstruction should be performed in younger patients, providing better longstanding functional results, whereas in older patients, endoprosthetic reconstruction should be preferred because of lower complication rates.…”
Section: Discussionmentioning
confidence: 99%